2004
DOI: 10.1016/j.jacc.2003.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial positron emission computed tomographic images obtained with fluorine-18 fluoro-2-deoxyglucose predict the response of idiopathic dilated cardiomyopathy patients to beta-blockers

Abstract: It has been shown that FDG-PET is a good predictor for the effectiveness of beta-blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…A number of clinical studies have strongly indicated the link between insulin resistance and nonischemic HF (23)(24)(25)(26). Approximately two-thirds of patients with essential hypertension have abnormal glucose metabolism (27), and there is a positive relationship between cardiac hypertrophy and the plasma insulin concentration (28), suggesting that elevation of insulin contributes to myocardial growth in the presence of chronic pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical studies have strongly indicated the link between insulin resistance and nonischemic HF (23)(24)(25)(26). Approximately two-thirds of patients with essential hypertension have abnormal glucose metabolism (27), and there is a positive relationship between cardiac hypertrophy and the plasma insulin concentration (28), suggesting that elevation of insulin contributes to myocardial growth in the presence of chronic pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that these effects are perhaps the most important reasons for the beneficial effects of long-term β-blocker treatment in patients with CHF and coronary heart disease. Indeed, it has been shown that estimation of glucose metabolism may select good responders to β-blocker treatment [18]. The aim of the present study was to establish whether central inhibition of sympathetic activity can produce additional similar changes in myocardial metabolism.…”
Section: Effects On Myocardial Metabolismmentioning
confidence: 91%
“…The potent adrenergic-blocking medication carvedilol, the only beta-blocker approved for HF that does not worsen insulin resistance, is 3 times as likely to cause a dramatic improvement in left ventricular function in the nonischemic cardiomyopathy population as in the ischemic cardiomyopathy population (32). Intriguingly, this degree of response to antiadrenergic therapy can be predicted by the severity of baseline abnormalities in myocardial glucose uptake (33).…”
Section: Clinical Evidencementioning
confidence: 99%